Ranging Behaviour of Commercial Free-Range Laying Hens - Leonard Ikenna Chielo (Animals, 2016)
In this study, the range use and behaviour of laying hens in commercial free-range flocks was explored. Six flocks were each visited on four separate days and data collected from their outdoor area (divided into zones based on distance from shed and available resources). These were: apron (0–10 m from shed normally without cover or other enrichments); enriched belt (10–50 m from shed where resources such as manmade cover, saplings and dust baths were provided); and outer range (beyond 50 m from shed with no cover and mainly grass pasture). Data collection consisted of counting the number of hens in each zone and recording behaviour, feather condition and nearest neighbour distance (NND) of 20 birds per zone on each visit day. In addition, we used techniques derived from ecological surveys to establish four transects perpendicular to the shed, running through the apron, enriched belt and outer range. Number of hens in each 10 m × 10 m quadrat was recorded four times per day as was the temperature and relative humidity of the outer range. On average, 12.5% of hens were found outside. Of these, 5.4% were found in the apron; 4.3% in the enriched zone; and 2.8% were in the outer range. This pattern was supported by data from quadrats, where the density of hens sharply dropped with increasing distance from shed. Consequently, NND was greatest in the outer range, least in the apron and intermediate in the enriched belt. Hens sampled in outer range and enriched belts had better feather condition than those from the apron. Standing, ground pecking, walking and foraging were the most commonly recorded activities with standing and pecking most likely to occur in the apron, and walking and foraging more common in the outer range. Use of the outer range declined with lower temperatures and increasing relative humidity, though use of apron and enriched belt was not affected by variation in these measures. These data support previous findings that outer range areas tend to be under-utilized in commercial free-range flocks and suggest positive relationships between range use, feather condition and increased behavioural opportunities and decline in the use of range in cold and/or damp conditions.